Converting waste lignin into nano-biochar as a renewable substitute of carbon black for reinforcing styrene-butadiene rubber. (1st February 2020) - Jiang, Can; Bo, Jinyu; Xiao, Xiefei; Zhang, Shumin; Wang, Zuhao; Yan, Guoping; Wu, Yanguang; Wong, Chingping; He, Hui
Graphical abstract: Highlights: Lignin was converted into biochar with high surface activity and high structure. LB presented a comparable reinforcing ability with CB, showing huge potential. The reinforcing ability of fillers depended on the structure and surface activity. The utilization of LB in rubber opens up a new path for the disposal of lignin. Abstract: Industrial waste lignin was commonly burnt or discharged into river in the past. However, in this study, lignin has been converted into high value-added nano-biochar as a renewable reinforcing filler of styrene-butadiene rubber (SBR) by a simple high-temperature carbonization treatment. Herein, the physicochemical change in lignin before and after carbonization was investigated. It was found that lignin-derived biochar (LB) consisted of vesicle-like primary nanoparticles which were closely packed to form "high-structure" irregular fragments with a high specific surface area (83.41 m 2 /g). When incorporating LB into SBR, the tensile properties of LB/SBR composites were significantly improved. At the filler loading of 40 phr, the tensile strength and elongation at break of the rubber composite were improved up to 7.1-folds and 2.4-folds of pristine SBR, respectively. Compared to commercial carbon black (CB) N330, the LB showed a similar reinforcing effect on SBR. However, the analysis on the morphology, stress-strain behavior and dynamic mechanical behavior suggested distinct reinforcing mechanisms for LB- and CB-filled rubber composites, due to the difference in the surface properties and structural characteristic of fillers. This work showed the application potential of LB as a renewable substitute of CB in rubber industry and brought environmental and economic benefits for the disposal of lignin.